At cancer diagnosis: a 'window of opportunity' for behavioural change towards physical activity. A randomised feasibility study in patients with colon and breast cancer. Issue 11 (4th November 2013) - Møller, Tom; Lillelund, Christian; Andersen, Christina; Ejlertsen, Bent; Nørgaard, Lone; Christensen, Karl Bang; Vadstrup, Eva; Diderichsen, Finn; Hendriksen, Carsten; Bloomquist, Kira; Adamsen, Lis
Abstract : Introduction: Challenges exist in identifying, recruiting and motivating sedentary patients with cancer to initiate physical activity towards recommended levels. We hypothesise that the onset period of adjuvant chemotherapy can be 'the open window of opportunity' to identify and motivate sedentary patients with breast and colon cancers, at risk for developing coronary heart disease, to initiate and sustain lifestyle changes. Aims: To investigate the feasibility of oncologists/nurses screening for physical inactivity, in order to identify and recruit an at-risk population of sedentary patients with breast or colon cancer at the onset of adjuvant chemotherapy. Furthermore, the study will examine the adherence to one of two multimodal exercise interventions lasting 12 weeks; (1) hospital-based, high intensity, group exercise intervention (2) home-based, low intensity, individual, pedometer intervention. Both arms will be compared with a control group. Methods and analyses: All newly referred patients will be screened for sedentary behaviour, using national recommendations. Testing at baseline, 6, 12 and 39 weeks will include; (1) physiological testing (VO2 -peak, one repetition maximum muscle strength and lung function (2) fasting full body dual-energy X-ray absorptiometry scan (3) fasting blood glucose, insulin, lipids and cholesterols, (4) psychometric questionnaires (general well-being, quality of life, anxiety and depression, motivational readiness). The randomised controlled trial feasibility design is selected in order to examine barriers for recruitment, programme adherence, safety aspects and potential efficacy to the interventions during adjuvant chemotherapy. Ethics and dissemination: The Scientific Committee of the Capital Region (case No. H-1-2011-131) and the Danish Data Protection Agency (j. No. 2011-41-6349) approved the study. Data will be entered and locked into a database hosted by the Copenhagen Trial Unit, Rigshosptialet. Data will be available for analyses to project members and the trial statistician after the 45 included patients have completed the 12-week test. Results will be published in peer-reviewed scientific journals. Trial registration: Current Controlled Trials ISRCTN24901641 .